2020
DOI: 10.3748/wjg.v26.i38.5849
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal decrease in platelet counts as a surrogate marker of liver fibrosis

Abstract: BACKGROUND Liver cirrhosis is a significant source of morbidity and mortality worldwide. The disease is usually indolent and asymptomatic early in its course while many cirrhotic patients are diagnosed late when severe complications occur. A major challenge is to diagnose advanced fibrosis as early as possible, using simple and non-invasive diagnostics tools. Thrombocytopenia represents advanced fibrosis and portal hypertension (HTN) and most non-invasive scores that predict liver fibrosis incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…The inverse association of BMI with platelet count is most likely related to liver damage and fibrosis resulting from liver fat infiltration, which in more extreme cases leads to non-alcoholic fatty liver disease (NAFLD) [ 44 ] and would further be aggravated by liver damage related to older age, high alcohol consumption, and smoking. Low platelet count is, indeed, a hallmark of fibrosis associated with cirrhosis and gradually decreases for several years prior to the overt clinical presentation of the disease [ 45 ]. Correspondingly, platelet count is included in most non-invasive liver fibrosis indices [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inverse association of BMI with platelet count is most likely related to liver damage and fibrosis resulting from liver fat infiltration, which in more extreme cases leads to non-alcoholic fatty liver disease (NAFLD) [ 44 ] and would further be aggravated by liver damage related to older age, high alcohol consumption, and smoking. Low platelet count is, indeed, a hallmark of fibrosis associated with cirrhosis and gradually decreases for several years prior to the overt clinical presentation of the disease [ 45 ]. Correspondingly, platelet count is included in most non-invasive liver fibrosis indices [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, they also play an important role in the disease prognosis. The association between PLT count trajectories and outcomes has been reported in several diseases, including severe coronavirus disease 2019 [ 23 ], liver fibrosis [ 24 ], and severe burns [ 25 ]. However, the novel finding was that the dynamic trajectory of PLT count was a significant predictor of all-cause mortality in patients with acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate Thrombocytopenia (50,000/μL-75,000/μL) was noted in approximately 13% of cirrhotic patients. There was a strong association between chronic liver disease and thrombocytopenia in 58% patients coming to the OPD in all the hospitals 6 In recent study 7 published in 2020, most common cause of liver disease was observed as viral infection (48%), alcoholic liver disease (24%) followed by NAFLD (20%). In the cirrhosis group, males had a mean platelet count of 210000 decreasing to 170000/μL vs females, with a mean number of platelets 250000 decreasing to 215000/μL.…”
Section: Discussionmentioning
confidence: 98%